More brain-powered science teaching and learning with discrepant events - O'Brien, Thomas 1956- (NSTA Press, 2011)
"Author Thomas O'Brien uses these and 20 other inquiry-oriented discrepant events?hands-on explorations or demonstrations in which the outcomes are not what students expect?to challenge students? preconceived ideas and urge them to critically examine the empirical evidence, draw logical inferences, and skeptically review their initial explanations with their peers. More Brain-Powered Science is the perfect dual-purpose activity book for grade 5?12 science teachers who aim to stimulate and motivate their students while expanding their own scientific understanding. Each activity will help bridge the gap between practice and theory for both students and teachers by relating conclusions to science concepts and pedagogical principles."--Publisher's description.